Group techniques as a methodological strategy in acquiring teamwork abilities by college students - César Torres Martín; María Julia Gámez Montalvo (Universidad de Granada, 2013)
From the frame of the European Higher Education Space an adaptation of teaching-learning process is being promoted by means of the pedagogical renewal, introducing into the class a major number of active or participative methodologies in order to provide students with a major autonomy in said process. This requires taking into account the incorporation of basic skills within university curriculum, especially "teamwork". By means of group techniques students can acquire interpersonal and cognitive skills, as well as abilities that will enable them to face different group situations throughout their academic and professional career. These techniques are necessary not only as a methodological strategy in the classroom, but also as a reflection instrument for students to assess their behavior in group, with an aim to modify conduct strategies that make that relationship with others influences their learning process. Hence the importance of this ability to sensitize students positively for collective work. Thus using the research-action method in the academic classroom during one semester and making systematic intervention with different group techniques, we manage to present obtained results by means of an analysis of the qualitative data, where the selected instruments are group discussion and personal reflection.